Modern trends in surgical treatment of liver echinococcosis - G. H. Musaev; V. V. Levkin; R. H. Sharipov (Сеченовский вестник)
The article presents literature review about surgical treatment of liver hydatidosis. Particular attention is paid to the development of percutaneous treatment. Also modern trend of surgical treatment are described. We presented results of percutaneous treatment of liver hydatidosis in our clinic. We analized them and made the conclusion that percutaneous treatment is eﬀective and safe method for liver hydatidosis. To reduce the risk of recurrence we have to do it right and all patients must take anti-relapse chemotherapy.